THE ORTHODONTIC TOOTH MOVEMENT: CAN BE ACCELERATED? - , MUHAMMAD NURUL AMIN ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
An orthodontic appliance is used to correct malocclusion, where the orthodontic tooth movement requires alveolar bone remodeling process. On the other hand, orthodontic appliance used to move tooth in the correct position is a process that takes a long time and requires a visit to the activation appliance repetitive and pain that make it uncomfortable, causing most patients are not cooperative and do not continue treatment that has been carried out. With these deficiencies, then for the acceleration of tooth movement requires some efforts to intervene the process of alveolar bone remodeling.